2007
DOI: 10.3354/dao01827
|View full text |Cite
|
Sign up to set email alerts
|

Site preference of myxozoans in the kidneys of Hungarian fishes

Abstract: Myxozoans are common parasites of fish kidneys, with most having specific sites of development. Five specific sites of development include (1) the lumen of renal tubules, (2) the renal corpuscles followed by location in renal tubules, (3) intracellular location within the tubular epithelium followed by a stage in the lumen of the ducts, (4) haematopoietic tissue with dispersed trophozoites, and (5) haematopoietic tissue with large, localized plasmodia. A coelozoic development preceded by presporogonic multipli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Scale bar = 2 µm sponse vary greatly depending on the host species (Padrós et al 2001, Álvarez-Pellitero et al 2008, Fleurance et al 2008. Similarly, the current results on turbot enteromyxosis demonstrated that the inflammatory response in the digestive tract was not always correlated with the number of parasites populating the epithelium, as has been previously reported (Bermúdez et al 2006b, 2007). An interesting finding was the initial increase in the amount of both rodlet and goblet cells, followed by a decrease in their number in fish suffering severe infections (Vigliano et al 2004).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Scale bar = 2 µm sponse vary greatly depending on the host species (Padrós et al 2001, Álvarez-Pellitero et al 2008, Fleurance et al 2008. Similarly, the current results on turbot enteromyxosis demonstrated that the inflammatory response in the digestive tract was not always correlated with the number of parasites populating the epithelium, as has been previously reported (Bermúdez et al 2006b, 2007). An interesting finding was the initial increase in the amount of both rodlet and goblet cells, followed by a decrease in their number in fish suffering severe infections (Vigliano et al 2004).…”
Section: Discussionsupporting
confidence: 84%
“…Although the vast majority of Myxosporea develops in any part of the fish body (Lom & Dyková 1995, Molnár 2007, few of them are described from enteric locations (Lom & Dyková 1995, Padrós et al 2001, Álvarez-Pellitero et al 2008. Ceratomyxa shasta, causing an important disease in salmonids, invades the intestinal epithelium, though the infection may become disseminated to several organs (Bartholomew et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the occurrence and development of these parasites can be attributed to a specific part or tissue of this organ. Five major sites of infection were distinguished (Molnár 2007). Most coelozoic myxozoans developing spores in the kidney have a presporogonic stage in the blood or in the renal glomeruli before sporogony in the kidney tubules or in the ureter.…”
Section: Infections In Kidneymentioning
confidence: 99%
“…plays an essential role in antigen trapping (Press, 1998) while the kidney, receiving the vast majority of postbranchial blood is expected to receive all pathogens present in the blood. Accounts on fish host and organ specificity of myxosporidia species are often confusing (Molnár, 2002(Molnár, , 2007, including those concerning species of the genus Myxobolus. Whereas sporogenesis of some coelozoic species was originally described in the kidney, other authors observed that spores of some histozoic species, secondarily occur in haematopoietic organs (Molnár, 2007).…”
mentioning
confidence: 99%
“…Accounts on fish host and organ specificity of myxosporidia species are often confusing (Molnár, 2002(Molnár, , 2007, including those concerning species of the genus Myxobolus. Whereas sporogenesis of some coelozoic species was originally described in the kidney, other authors observed that spores of some histozoic species, secondarily occur in haematopoietic organs (Molnár, 2007). According to Dyková (1984), myxospores are generally transported by macrophages homing on macrophage centers of haematopoietic organs, where they are destroyed.…”
mentioning
confidence: 99%